Penguatan Kapasitas Guru dan Konselor Sebaya: Deteksi dan Penatalaksanaan Dini Kesehatan Mental-Emosional Siswa - Kusumaratna, Rina Kurniasri; Said, Putri Melinda; Rifky, Muhammad; Hasan, Debra Alliya Dalil; Suci, Witriastika (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
Adolescents are known to be more vulnerable to mental health issues due to the emotional upheaval that characterizes the transition from childhood to adulthood. Globally, 1 in 7 adolescents experiences emotional mental health problems, mainly anxiety and depression. The Indonesia National Adolescence Mental Health Survey (I-NAHMS) reports that one in three Indonesian adolescents faces mental health issues, and one in twenty suffers from mental disorders. Early screening and intervention are crucial due to the high risk and significant impact of these problems. Raising awareness among the community, especially within schools, about adolescent emotional mental health is essential. This activity uses the Health Promotion Model, targeting three guidance counseling teachers and 61 peer counselors from grades X and XI at a public high school in South Jakarta. Training showed improvements in understanding and knowledge of guidance-counceling’ teachers and peer counselors (p=0.00), and in conducting assessments using the e-SDQ instrument for screening and psychological first aid. This enables early intervention for adolescents’ emotional mental issues before referral to the PKPR clinic at the community health center.